A review: microbiological, physicochemical and health impact of high level of biogenic amines in fish sauce - Zaman, Muhammad Zukhrufuz; Abdulamir, Ahmed Sahib; Abu Bakar, Fatimah; Selamat, Jinap; Bakar, Jamilah (Science Publications, 2009)
Problem statement: Biogenic amines are basic nitrogenous compounds present in a wide variety of foods and beverages. Their formations were mainly due to the amino acids decarboxylase activity of certain microorganisms. Excessive intake of biogenic amines could induce many undesirable physiological effects determined by their psychoactive and vasoactive action. Fish sauce which is considered as a good source of dietary protein, amino acids, vitamins and minerals was a popular condiment in Southeast Asian countries. However, it has also been reported that fish sauce contain high amount of amines. Hence, attention should be given to ensure the safety of this product. Approach: A review study was conducted to deliver an overview on the presence of biogenic amines in fish sauce and to discuss the important factors affecting their accumulation. Impact of amines on human health and efforts to reduce their accumulation in fish sauce were also discussed to give a comprehensive view. Results: Histamine, putrescine and cadaverine is the most abundant amines in fish sauce with maximum reported value of 1220, 1257 and 1429 ppm, respectively. Tyramine present in a lesser amount with maximum reported value of 1178 ppm. Other amines such as tryptamine, phenylethylamine, spermine and spermidine were considered as minor amines. However, different profiles of amines were reported in different type of products. This was depended on microbial flora, availability of precursors and physicochemical factors such as temperature, pH, salt, oxygen and sugar concentration. In synergistically supporting physicochemical factors, several microorganisms such as Enterobacteriaceae, Micrococci and Lactobacilli were responsible for biogenic amines formation in fish sauce. Conclusion: Since the formation of amines in fish sauce was a result of many factors, it was almost virtually impossible to control each factor during fermentation. Addition of amines degrading bacteria into fish sauce fermentation might be useful to prevent amines accumulation. Concomitantly, a good and hygienic manufacturing procedure will enhance the safety of fish sauce.